Physical properties of concrete with 5.0 and 10.0 percent palm oil boiler stone (POBS) as fine aggregate replacement - Nur Amalina, Mohamad Yuden (2010)
It has been more than a decade since the understanding and use of waste material was developed. The behavior and promising desired characteristic led to many studies and research work to reveal the potential of this material as suitable, safe and economical building material. One of the many challenges of research work in engineering material is to improve the material in different ways to obtain a better product. The palm oil boiler stone (POBS) is a new waste material and abundantly available has the potential as a replacement for fine aggregates in the production of concrete. This study investigates the effects of substitution of POBS aggregates towards the physical properties of concrete which consist of workability and compressive strength as a primary physical property. Three types of samples were prepared with the constant water/cement ratio (w/c) of 0.57 and POBS content of 0%, 5% and 10% in concrete. A total of 27 concrete cube specimens 150 mm x 150 mm x 150 mm were prepared for standard testing. The tests that were conducted are slump test, compacting factor test and concrete compression test at curing age of 7, 14 and 28 days. The result of this study indicates that the substitution of POBS aggregates in concrete increases the workability and strength of concrete. This study indicates that concrete with POBS content can be used for load bearing purposes due to high strength.